The History of Nursing Research and the Process of Capacity-Building in Nursing Research - Masoud Fallahi Khoshknab (Tehran University of Medical Sciences, 2014)
Nearly a century has passed since the establishment of nursing education programs in Iran. The first nursing school was established in 1916 (1294 Solar Hijri) in Urmia and moved to Tabriz after a year due to the World War.   Also, nursing research in Iran has a history of nearly half a century. Nursing research in Iran first began independently in 1970s (1350s SH) with starting admission in master of nursing by nursing schools. Before that, nurses usually participated in studies as an assistant. Most nursing research in this decade included descriptive research performed by master students as their dissertations which were mainly guided by non-nurse supervisors.   In 1980s (1360s SH), nursing research became more analytical and nurses began to analyze the contributing factors in addition to their description and conduct epidemiological studies. The research findings were often presented in medical congresses, however few scientific congresses were held by nursing and midwifery schools in this decade which had significant role in current status of nursing research.